Sosialisasi Pemanfaatan Kulit Telur Sebagai Pupuk Organik di Desa Weuh Krueng Kecamatan Montasik - Khumaira; Puspita, Diah Eka; Rijal, Khairin; Aulia, Kamila (Yayasan Sagita Akademia Maju, 2025)
This community service activity aimed to enhance the understanding of residents in Weuh Krueng Village, Montasik Subdistrict, regarding the utilization of eggshell waste as organic fertilizer. The program was carried out through counseling and demonstrations on producing liquid organic fertilizer (LOF) from eggshells, which are rich in calcium, phosphorus, magnesium, and potassium, thereby improving soil quality and supporting plant growth. The activities, conducted from August to September 2025, involved lecturers, community service students, and local residents. The results indicated a high level of community enthusiasm, as participants gained knowledge of the benefits of eggshells both in reducing household waste and as an alternative to chemical fertilizers. This program provided the community with new skills that support environmentally friendly farming and offer economic potential through productive household waste management.